Two clip-domain serine protease homologs, cSPH35 and cSPH242, act as a cofactor for prophenoloxidase-1 activation in Drosophila melanogaster - Jin, Qiao; Wang, Yang; Yin, Haodong; Jiang, Haobo (Frontiers in Immunology, 2023)
Insect phenoloxidases (POs) catalyze phenol oxygenation and o-diphenol oxidation to form reactive intermediates that kill invading pathogens and form melanin polymers. To reduce their toxicity to host cells, POs are produced as prophenoloxidases (PPOs) and activated by a serine protease cascade as required. In most insects studied so far, PPO activating proteases (PAPs) generate active POs in the presence of a high Mr cofactor, comprising two serine protease homologs (SPHs) each with a Gly residue replacing the catalytic Ser of an S1A serine protease (SP). These SPHs have a regulatory clip domain at the N-terminus, like most of the SP cascade members including PAPs. In Drosophila, PPO activation and PO-catalyzed melanization have been examined in genetic analyses but it is unclear if a cofactor is required for PPO activation. In this study, we produced the recombinant cSPH35 and cSPH242 precursors, activated them with Manduca sexta PAP3, and confirmed their predicted role as a cofactor for Drosophila PPO1 activation by MP2 (i.e., Sp7). The cleavage sites and mechanisms for complex formation and cofactor function are highly similar to those reported in M. sexta. In the presence of high Mr complexes of the cSPHs, PO at a high specific activity of 260 U/μg was generated in vitro. To complement the in vitro analysis, we measured hemolymph PO activity levels in wild-type flies, cSPH35, and cSPH242 RNAi lines. Compared with the wild-type flies, only 4.4% and 18% of the control PO level (26 U/μl) was detected in the cSPH35 and cSPH242 knockdowns, respectively. Consistently, percentages of adults with a melanin spot at the site of septic pricking were 82% in wild-type, 30% in cSPH35 RNAi, and 53% in cSPH242 RNAi lines; the survival rate of the control (45%) was significantly higher than those (30% and 15%) of the two RNAi lines. These data suggest that Drosophila cSPH35 and cSPH242 are components of a cofactor for MP2-mediated PPO1 activation, which are indispensable for early melanization in adults.